Comparative Assessment of the Life History Parameters of Moina Macrocopa Raised on Indigenous Culture Media - Jignesh N. Mevada (KUFOS, 2019)
Abstract- The main goal of this study was to determine the effect of stocking density and culture medium on the life table parameters of Moina macrocopa. Substrates assessed were GNOC, COC, WB and Yeast. Two feed levels tried were 0.25 and 0.5. The study was done in two segments. In the first set, the population developed at stocking density of 10 nos. was assessed. In the second set four stocking densities were tried. Four substrates were given at two feed levels. Stocking density was highly significant (p<0.05) in GNOC, COC, WB and Yeast medium. Feed level was significant in GNOC and Yeast. Growth of Moina was observed to be higher in GNOC medium. Life table parameters like Longevity, 1st reproduction, Total Offspring produced by single mother, Reproduction peak, Reproductive life span were taken. For collecting life table data, single neonate was inoculated in petri dish. Life table data was collected every day by examined each petri dish. Higher longevity was observed in GNOC, Yeast and a greater number of offspring produced by single mother and long reproductive life span was observed in Yeast medium. Early reproduction Peak was observed in GNOC medium on 5th day.